Digitalization of Romanian public administration: a panel data analysis at regional level - Frățilă, Alexandra; Păunescu, Mirela; Nichita, Elena-Mirela; Lazăr, Paula (Journal of Business Economics and Management, 2023)
Digital transformation of public administration creates opportunities for transparency, accountability, efficiency, and better tax collection. Benefits are even more critical considering the coronavirus crisis when millions of people worldwide engage in online solutions. Our research paper offers clear insights into the public administrations’ strategic management when it comes to the impact of digitalization upon local tax revenues collection. In this setting, we investigate the effects of the digitalization of the Romanian public sector, focusing on local tax revenues collection covering the period 2015–2021. The data was collected from the national platform for e-payments – ghiseul.ro. To assess the impact of digitalization, we opted for the panel data analysis, complemented by reliability and robustness tests. The local tax revenues are settled as the dependent variable and analysed in relationship with the number of payments made via the above-mentioned platform  (assigned as a proxy for digitalization). Gross domestic product per capita, Unemployment rate, and Average net earnings are control variables. Our outcomes show that digitalization impacts local tax revenues, but it differs across the country, the highest impact being registered in the case of macroregion 3. All independent variables are statistically significant, leading to the assumption that the empirical model is accurate.